2018
DOI: 10.1021/acs.jced.7b00797
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Protocatechuic Acid Using Di-(2-ethylhexyl)phosphoric Acid in Isobutyl Acetate, Toluene, and Petroleum Ether

Abstract: Protocatechuic acid has potential pharmacological significance, like antioxidant, antibacterial, and anticancer activity. The extraction of carboxylic acids from dilute aqueous phase is a topic of current interest to researchers. The present equilibrium study deals with the reactive extraction of protocatechuic acid from an aqueous solution by using di-(2-ethylhexyl)phosphoric acid (D2EHPA) in diluents, such as isobutyl acetate (IBA), toluene, and petroleum ether at isothermal conditions (298 ± 1 K). The physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…The (S/F) min for reactive separation of malonic acid using extractant (TBP) with diluents was evaluated. The value of (S/F) min depends on the initial malonic acid concentration, and according to a well-known rule in extraction processes, (S/F) act is proportional to 1.5 times (S/F) min …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The (S/F) min for reactive separation of malonic acid using extractant (TBP) with diluents was evaluated. The value of (S/F) min depends on the initial malonic acid concentration, and according to a well-known rule in extraction processes, (S/F) act is proportional to 1.5 times (S/F) min …”
Section: Results and Discussionmentioning
confidence: 99%
“…The value of (S/F) min depends on the initial malonic acid concentration, and according to a wellknown rule in extraction processes, (S/F) act is proportional to 1.5 times (S/F) min . 52 The number of theoretical stages required for separation of malonic acid in countercurrent fashion was evaluated using a modified Kremser equation:…”
Section: Comparison Of Model and Experimental Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some literature is availabile on the equilibrium studies on the reactive separation of PCA [34,35,36,37,38]. Apart from reactive extraction, for the retrieval of PCA from the aqueous waste stream of food processing industries, the methods in practice till date includes microbial degradation [39], ultrafiltration [40], adsorption [41], H 2 O 2 /UV or O 3 /UV [42], etc., each of the methods facing its own merits as well as certain limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Pandey et al, have shown the effect of polarity of solvents (MIBK, octanol, kerosene, decane) and type of extractant (TOA, TBP) on the extraction of gallic acid . The literature shows that, apart from that for gallic acid, few other reactive extraction studies on other phenolic acids such as benzoic acid and protocatechuic acid have been carried out.…”
Section: Introductionmentioning
confidence: 99%